“CIRCULAR ECONOMY PRACTICES IN AN ECOVILLAGE” (An Overview of Circular Economy Practices in Bendungan Village, West Java, Indonesia) - Dafi Dinansyah Wiradimadja (UNIVERSITAS KEBANGSAAN, 2018)
Abstract: Environmental problems have been increasing globally, especially after the industrial revolution as S.Barles stated. One of the problem in Indonesia that has become an international concern in plastic waste. Based on World Bank statement, Indonesia in 2018 has become world’s second largest plastic waste producer in the world. Borgen Project also stated that Indonesia is estimated to contribute roughly 200,000 tons of waste from its rivers and streams. Bendungan Village, the location of this research is passed by Ciliwung River. The location of this village has made the West Java Government distress concerning the Ciliwung River, the government is afraid that the river will worsened by the plastic waste, thus the government made the ecovillage program to solve the problem. One of the program that can solve the plastic wastes problem in this village is through circular economy. This research used Mixed Methods approach as it research methods. Based on the existing problems, one of the ecovillage program relating to the improvement of environmental issues are through the method of circular economy. Parameters of the circular economy are: the role of garbage bank to the circular economy input; community’s income through garbage bank; utilization of agricultural waste into new commodities such as an organic fertilizer; the use of plastic waste for the village’s economic benefit. The result shows that the program has helped the village people to gain economic benefit from wastes and also has helped to clean the environment. Keywords: Circular Economy, Ecovillages, West Java, Ciliwung River, Bendungan Village, Waste Abstrak: Masalah lingkungan telah meningkat secara global, terutama setelah revolusi industri seperti yang dinyatakan S.Barles. Salah satu masalah lingkungan di Indonesia yang telah menjadi perhatian internasional dalam limbah plastik. Berdasarkan pernyataan Bank Dunia, Indonesia pada tahun 2018 telah menjadi penghasil sampah plastik terbesar kedua di dunia. Proyek Borgen juga menyatakan bahwa Indonesia diperkirakan menyumbang sekitar 200.000 ton limbah dari sungai dan sungainya. Desa Bendungan, lokasi penelitian ini dilalui oleh Sungai Ciliwung. Lokasi desa ini telah membuat Pemerintah Jawa Barat tertekan dengan Sungai Ciliwung, pemerintah khawatir sungai akan memburuk oleh sampah plastik, sehingga pemerintah membuat program ecovillage untuk menyelesaikan masalah. Salah satu program yang dapat menyelesaikan masalah sampah plastik di desa ini adalah melalui circular economy. Penelitian ini menggunakan metode Mixed Methods dengan metode penelitian. Berdasarkan permasalahan yang ada, salah satu program ecovillage yang berkaitan dengan perbaikan isu lingkungan adalah melalui metode ekonomi lingkaran. Parameter circular economy adalah: peran bank sampah dalam circular economy; pendapatan masyarakat melalui bank sampah; pemanfaatan limbah pertanian menjadi komoditas baru seperti pupuk organik; penggunaan sampah plastik untuk keuntungan ekonomi desa. Hasil penelitian menunjukkan bahwa program tersebut telah membantu penduduk desa untuk mendapatkan manfaat ekonomi dari limbah dan juga telah membantu membersihkan lingkungan. Kata kunci: Circular Economy, Ecovillages, Jawa Barat, Sungai Ciliwung, Desa Bendungan, Limbah, Sampah